Differences in macrobenthic faunal communities in mangrove wetland habitats (Zhanjiang, China) invaded and non‐invaded by exotic cordgrass Spartina alterniflora. Issue 6 (29th May 2018) - Chen, Quan; Jian, Shuguang; Ma, Keming; Chen, Pimao
Abstract: Mangroves are essential for maintaining local biodiversity and human well‐being, and mangrove structure and functioning depend on the macrobenthos. Although exotic cordgrass, Spartina alterniflora, is an increasing threat to the mangrove wetlands (including the associated unvegetated shoals) of China, its effects on the macrobenthic fauna in such wetlands is poorly understood. The macrobenthic faunal communities were compared in (1) an Avicennia marina monoculture vs. an S. alterniflora ‐invaded A. marina stand (a mixture of A. marina and S. alterniflora ) and in (2) an unvegetated shoal vs. an S. alterniflora ‐invaded shoal that had rapidly become an S. alterniflora monoculture in Zhanjiang, China. S. alterniflora invasion significantly increased plant density regardless of invaded habitat but significantly increased the contents of total carbon, organic matter, and total sulfur in the sediment only in the unvegetated shoal. The presence of S. alterniflora had little influence on indices of the macrobenthic faunal community in the A. marina monoculture, but significantly decreased the density and biomass of macrobenthic faunal community in the unvegetated shoal. These results indicate that the effects of S. alterniflora on the macrobenthic faunal community depend on which type of mangrove habitat is invaded. The composition of the macrobenthic faunal community was more similar between the invaded and non‐invaded A. marina stand than between the invaded and non‐invaded unvegetated shoal. Overall, the differences in the macrobenthic faunal community between invaded and non‐invaded habitats were associated with increases in the sediment organic matter content and plant density.